Peer power : preadolescent culture and identity - Adler, Patricia A. (Rutgers University Press, 1998)
Peer Power explodes existing myths about children's friendships, power, and popularity, and the gender chasm between elementary school boys and girls. Based on eight years of intensive insider participant observation in their own children's community, the authors discuss the vital components in the lives of preadolescents: popularity, friendships, cliques, social status, social isolation, loyalty, bullying, boy-girl relationships, and afterschool activities. They describe how friendships shift and change, how children are drawn into groups and excluded from them, how clique leaders maintain their power and popularity, and how the individuals' social experiences and feelings about themselves differ from the top of the pecking order to the bottom. The Adlers focus their attention on the peer culture of the children themselves and the way this culture extracts and modified elements from adult culture. Children's peer culture, as it is nourished in those spaces where grownups cannot penetrate, stands between individual children and the larger adult society. As such, it is a mediator and shaper, influencing the way children collectively interpret their surroundings and deal with the common problems they face. The Adlers explore some of the patterns that develop in this social space, noting both the differences in the gendered cultures of boys and girls and their overlap into afterschool activities, role behavior, romantic inclinations, and social stratification. Peer culture contains the informal social mechanisms through which children create their social order, determine their place and identity, and develop positive and negative feelings about themselves.